Thyme (Thymus vulgaris L.) polyphenols ameliorate DSS-induced ulcerative colitis of mice by mitigating intestinal barrier damage, regulating gut microbiota, and suppressing TLR4/NF-κB-NLRP3 inflammasome pathways. Issue 2 (3rd January 2023) - Zhou, Zuman; He, Wanying; Tian, Honglei; Zhan, Ping; Liu, Jianshu
Abstract : Thyme ( Thymus vulgaris L.) is an important medicinal and edible homologous plant, and the composition and bioactivity of its polyphenol extracts have attracted widespread attention from researchers. Abstract : Thyme ( Thymus vulgaris L.) is an important medicinal and edible homologous plant, and the composition and bioactivity of its polyphenol extracts have attracted widespread attention from researchers. In this study, the polyphenols in thyme were separated and identified by UPLC/MS-MS and UPLC-DAD, and the intervention effect and mechanism of thyme polyphenols (TP) on ulcerative colitis (UC) were analyzed in combination with dextran sulfate sodium salt (DSS)-induced mice colitis model. It was found that the main substances of TP were scutellarin (160.68 ± 2.09 mg g −1 ), rosmarinic acid (80.33 ± 1.74 mg g −1 ), scutellarein (56.53 ± 1.32 mg g −1 ), apigenin-7- O -glucuronide (21.06 ± 0.68 mg g −1 ), gallic acid (13.80 ± 0.73 mg g −1 ), and ferulic acid (12.00 ± 0.20 mg g −1 ). TP and sulfasalazine, which were respectively supplemented to these experimental mice at 200 mg per kg bw and 100 mg per kg bw, showed similar effects on alleviating intestinal inflammation, as indicated by the consistency of the decreased NLRP3 and TLR4 proteins and inhibited pro-inflammatory cytokine secretion in NF-κB inflammatory signaling pathway. Furthermore, the treatment with TP at doses of 200 and 400 mg per kg bw both effectively upregulated tight junction protein expression and enhanced intestinal epithelial cell integrity. Consistently, the abundany of probiotics including Blautia, Bacteroides, Romboutsia, and Faecalibaculum associated with the synthesis of short chain fatty acids (SCFAs) were elevated, whereas harmful bacteria including Escherichia Shigella, Muribaculum, and Clostridium sensu stricto 1 associated with the inflammatory process were significantly inhibited. Notably, TP supplemented at the dose of 100 mg per kg bw showed weak mitigated effects on the above symptoms, while the other two TP experimental groups showed similar promising therapeutic potential, suggesting that such beneficial effects required a certain dose of TP to be achieved. These results indicated that TP could suppress the TLR4/NLRP3-NF-κB inflammasome pathways, protect the intestinal epithelial barrier, and remodel the disordered gut microbiota, which suggested that TP might be a promising dietary strategy for UC.